Institutional Quality and its Impact on FDI Inflow: Evidence from the EU Member States - Dobrowolska, Bogusława; Dorożyński, Tomasz; Kuna‑Marszałek, Anetta (Comparative Economic Research. Central and Eastern Europe, 2021)
The aim of the article is to assess institutional quality in 28 EU Member States and to examine the relationship between the quality of institutions and FDI inward stock as % of GDP. This study is structured as follows. Firstly, we reviewed studies dedicated to the relationship between institutional quality and investment attractiveness. Then, we discussed FDI inflow into the EU countries and selected diagnostic variables that later served as the basis for our research in which we used categories of the Global Competitiveness Index. Based on rankings and using statistical methods, in the next stage, we divided the EU Member States into groups representing similar institutional quality. Then we investigated the relationships between groups of countries similar to one another when it comes to institutional quality and groups of countries ranked in ascending order by the value of foreign direct investment inflow measured as FDI inward stock as % of GDP. The study demonstrated that the EU Member States differ with respect to institutional quality. The results of the statistical analysis have provided grounds to positively verify the hypothesis about a positive relationship between the level of institutional quality and investment attractiveness.